Proceso de atención de enfermería en neonato con sepsis bacteriana, no especificada. - Romero Zúñiga, Julio Antonio (2023)
Title: Nursing care in the newborn with unspecified neonatal sepsis. Introduction: Neonatal morbidity and mortality in recent decades is mainly caused by prematurity; the number of new cases of preterm labor has failed to decrease; therefore, its incidence has been increasing and the survival of these very premature newborns have managed to survive thanks to the advances in intensive care units. In the world, in Latin America and the Caribbean, approximately 12 million children are born and likewise one million children die due to complications of their prematurity. Presentation of the case: neonate by smoke 28.4 sem/capurro 38 weeks. vaginal delivery, 24-year-old mother, with a previous delivery with a full-term product with withdrawal symptoms for which she was admitted to the La Libertad Basic Hospital; poorly controlled pregnancy, positive ORH group, non-reactive HIV-VDRL, negative tests for hepatitis A, B and C. Untreated recurrent urinary and vaginal infections during pregnancy, affirms consumption of heroin-type illicit substances, last dose 3 days before delivery, apgar score 8 points at one minute and 9 at five minutes, weight 2,890 grams, length 48 cm, head circumference 32 cm , chest circumference 32 cm, abdominal circumference 30 cm.